Optimisation of asexual propagation of two clones of Carob tree (Ceratonia siliqua L.) by aerial Marcottage in the eastern region of Morocco - Boulida Zaineb; Mzabri Ibtissam; Alla Anass; Mesbahi Qamar; Boukhaffa Chaymae; Arabi Mourad; Kouddane Noureddine; Berrichi Abdelbasset (E3S Web of Conferences)
Sexual propagation of the carob tree poses difficulties in terms of germination because of the tegumental dormancy of the seeds, its dioeciousness and the great genetic variability which complicates the conservation of the desired performances. In response to these limitations, asexual propagation is a promising approach for faithfully reproducing individuals with traits of interest to growers, while enabling rapid production of homogeneous plants. This study aims to optimise asexual propagation methods, using aerial layering, in order to clone high-performance genotypes, shorten the juvenile phase and speed up the production of vigorous, uniform plants. Our work was carried out on two cultivars : the RAHMA variety, a hermaphrodite cultivar, and another female clone selected in the town of Oujda. The results showed a success rate of 95.31% for the RAHMA variety and 80% for the female clone. These promising results show the effectiveness of the aerial layering method for cloning individuals or varieties with distinctive traits. This work highlights the potential of aerial layering as a reliable technique for propagating carob clones with specific genetic and phenotypic characteristics.